Differential regulation of amyloid precursor protein sorting with pathological mutations results in a distinct effect on amyloid‐β production. (13th August 2014) - Lin, Yen‐Chen; Wang, Jia‐Yi; Wang, Kai‐Chen; Liao, Jhih‐Ying; Cheng, Irene H.
Abstract The deposition of amyloid‐β (Aβ) peptide, which is generated from amyloid precursor protein (APP), is the pathological hallmark of Alzheimer's disease (AD). Three APP familial AD mutations (D678H, D678N, and H677R) located at the sixth and seventh amino acid of Aβ have distinct effect on Aβ aggregation, but their influence on the physiological and pathological roles of APP remain unclear. We found that the D678H mutation strongly enhances amyloidogenic cleavage of APP, thus increasing the production of Aβ. This enhancement of amyloidogenic cleavage is likely because of the acceleration of APPD678H sorting into the endosomal‐lysosomal pathway. In contrast, the APPD678N and APPH677R mutants do not cause the same effects. Therefore, this study indicates a regulatory role of D678H in APP sorting and processing, and provides genetic evidence for the importance of APP sorting in AD pathogenesis.<boxed-text content-type="graphic" id="jnc12829-blkfxd-0100" position="anchor" orientation="portrait"> </boxed-text> The internalization of amyloid precursor protein (APP) increases its opportunity to be processed by β‐secretase and to produce Amyloid‐β (Aβ) that causes Alzheimer's disease (AD). We report a pathogenic APPD678H mutant that enhances APP internalization into the endosomal‐lysosomal pathway and thus promotes the β‐secretase cleavage and Aβ production. This study provides genetic evidence for the importance of APP sorting in AD pathogenesis.